A comparison of visual scene and grid displays for people with chronic aphasia: a pilot study to improve communication using AAC. Issue 11 (2nd November 2017) - Brock, Kris; Koul, Rajinder; Corwin, Melinda; Schlosser, Ralf
ABSTRACT: Background : People with aphasia are using technology-based augmentative and alternative communication (AAC) devices to support their communication. Typically, messages in AAC devices are organised using the following two interfaces: (a) grid displays that organise symbols into semantic categories (e.g., food) and (b) scene displays that organise photographs contextually. However, there is no published research comparing the influence of these displays across communicative outcome variables. Aims : The purpose of this study was to explore the effect of a grid display and a scene display across several communicative variables (e.g., conversational turns) during conversational interactions with a communication partner (CP). Additionally, we investigated generalisation to an untrained second conversation in one of the two participants. Methods & Procedures : Two experiments were conducted, and each included a different participant with chronic Broca's aphasia. In Experiment 1, the participant watched an I Love Lucy episode and was trained to use the grid and scene displays for communicative purposes (e.g., formulating messages with the AAC device). After training, the participant engaged in conversations with a CP using either the grid display or the scene display. Experiment 2 followed the same procedures as Experiment 1; however, this participant watched a second I Love Lucy episode. She did not receive any grid display or scene display training for the second episode. The investigators examined (a) the total conversation time, (b) the number of conversational turns, instances of frustration, and navigational errors, (c) conceptual complexity of utterances, and (d) question response accuracy (measured as a percentage). Results : Descriptive analyses revealed that the participants' communicative outcomes were superior in the scene display conditions. Specifically, a greater number of conversational turns were taken with fewer instances of frustration and navigational errors. The utterances in the scene display conditions were longer and more complex than utterances in the grid display conditions. Probe question response accuracy was greater in the scene display condition in comparison with grid display condition. Conclusion : The experiments represent a preliminary attempt to measure communicative competence in persons with aphasia (PWA) using different displays. The results suggest that scene displays facilitate a greater number of conversational turns for PWA than the grid displays. Additionally, utterance complexity was greater in the scene display condition. However, these results are limited to two individuals with aphasia, and systematic replication is warranted.